REPRESENTASI GENDER MELALUI BAHASA DALAM NOVEL SALI: KISAH SEORANG WANITA SUKU DANI KARYA DEWI LINGGASARI - Sarina, Sarina (JURNAL ILMU BUDAYA, 2019)
This study aims to reveal the forms of injustice reflected through the language used in the novel of Sali: Kisah Seorang Wanita Suku Dani by Dewi Linggasari. This research is a study using descriptive methods. A method of study is a way of gaining knowledge of a particular object and therefore, must conform to the existence of the object as the theory states. The research Data is the language in the Sali’s Novel: Kisah Seorang Wanita Suku Dani by Dewi Langgasari. Data collection using documentation techniques and note-taking techniques. The results showed that: data on forms of gender injustices reflecting through the language in Sali's novel: Kisah Seorang Wanita Suku Dani, the researcher found only three of the five types of violence set in the previous chapter. The three forms of violence, namely discrimination, double burden, and violence. Also, subordination and marginalization are not found.